2011
DOI: 10.1038/nchembio.715
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical modulation of catalytic power on F1-ATPase

Abstract: The conformational fluctuation of enzymes has a crucial role in reaction acceleration. However, the contribution to catalysis enhancement of individual substates with conformations far from the average conformation remains unclear. We studied the catalytic power of the rotary molecular motor F(1)-ATPase from thermophilic Bacillus PS3 as it was stalled in transient conformations far from a stable pausing angle. The rate constants of ATP binding and hydrolysis were determined as functions of the rotary angle. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
165
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 99 publications
(197 citation statements)
references
References 45 publications
29
165
3
Order By: Relevance
“…The stator a 3 b 3 ring has the intrinsic cooperativity necessary to achieve rotary catalysis among the three catalytic sites. However, this result is not inconsistent with the observations that the rates and equilibriums of the F 1 reactions are controlled by the rotary angle of the c-subunit (14,18,(25)(26)(27). Without the c-subunit, the rate and efficiency of the unidirectional rotary catalysis was distinctly lower than that for F 1 .…”
Section: The Mechanism Supporting the Rotary Catalysis Of Fcontrasting
confidence: 53%
See 1 more Smart Citation
“…The stator a 3 b 3 ring has the intrinsic cooperativity necessary to achieve rotary catalysis among the three catalytic sites. However, this result is not inconsistent with the observations that the rates and equilibriums of the F 1 reactions are controlled by the rotary angle of the c-subunit (14,18,(25)(26)(27). Without the c-subunit, the rate and efficiency of the unidirectional rotary catalysis was distinctly lower than that for F 1 .…”
Section: The Mechanism Supporting the Rotary Catalysis Of Fcontrasting
confidence: 53%
“…Thus, it was proposed that interactions with the c-subunit control the conformational and catalytic states of each b-subunit to sequentially generate torque (24). The single-molecule manipulation experiments showed that by controlling the rotary angle of the c-subunit alone, the rate and equilibrium of the ATP hydrolysis/synthesis reaction on F 1 can be modulated and even reversed, and reinforced the contention (14,18,(25)(26)(27). These results caused the elevation of the c-subunit to the position of a ''dictator,'' completely controlling the reaction catalyzed by F 1 .…”
Section: The Mechanism Supporting the Rotary Catalysis Of Fmentioning
confidence: 95%
“…The linearity condition was not fulfilled for the ATP binding step but was roughly fulfilled for the hydrolysis although the present data are relatively sparse (Fig. 3c in Watanabe et al 2012).…”
Section: There Is a Harmonic Behavior Of The Restoring Forcementioning
confidence: 63%
“…A particular example would be to use a collision theory picture (Volkán-Kacsó & Marcus, 2015) of ATP binding to the weak binding site of an empty β subunit in which the pre-exponential term A is a collision frequency Z, and a term related to an ATP binding outside of the β subunit. For the binding and release of ATP there are extensive data obtained by different methods (Adachi et al 2012;Braig et al 2000;Spetzler et al 2009;Watanabe et al 2010Watanabe et al , 2012Yasuda et al 2001). In the ATP binding an ATP first forms a collision complex (Oster & Wang, 2000) with the F 1 -ATPase, followed by an ATP binding as the next step (an 80°step) in the overall hydrolysis.…”
Section: Rate Constants and Free Energy Relationsmentioning
confidence: 99%
See 1 more Smart Citation